2011
DOI: 10.1093/jxb/err234
|View full text |Cite
|
Sign up to set email alerts
|

Synergic effect of salinity and zinc stress on growth and photosynthetic responses of the cordgrass, Spartina densiflora

Abstract: Spartina densiflora is a C4 halophytic species that has proved to have a high invasive potential which derives from its physiological plasticity to environmental factors, such as salinity. It is found in coastal marshes of south-west Spain, growing over sediments with between 1 mmol l−1 and 70 mmol l−1 zinc. A glasshouse experiment was designed to investigate the synergic effect of zinc from 0 mmol l−1 to 60 mmol l−1 at 0, 1, and 3% NaCl on the growth and the photosynthetic apparatus of S. densiflora by measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…This might be caused by the formation of complexes between chloride and metals [74]. Redondo-Gomez et al [75] reported that salinity was promoted trace metals tolerance, through excretion metals in salt crystals liberated by salt glands in order to reduce its negative effects on cell metabolism. Bankaji et al [4] observed the same behaviour in two halophytic species Atriplex halimus and Suaeda fruticosa, which suggests an addition of NaCl to the irrigation solution can significantly reduce the endogenous Cd 2+ and Cu 2+ concentration in different tissues.…”
Section: As Uptakementioning
confidence: 99%
“…This might be caused by the formation of complexes between chloride and metals [74]. Redondo-Gomez et al [75] reported that salinity was promoted trace metals tolerance, through excretion metals in salt crystals liberated by salt glands in order to reduce its negative effects on cell metabolism. Bankaji et al [4] observed the same behaviour in two halophytic species Atriplex halimus and Suaeda fruticosa, which suggests an addition of NaCl to the irrigation solution can significantly reduce the endogenous Cd 2+ and Cu 2+ concentration in different tissues.…”
Section: As Uptakementioning
confidence: 99%
“…Therefore, S. alterniflora suffers relatively little damage from high salinity. Specifically, some scholars have reported that the photosynthesis of cordgrass does not significantly change in the salinity range of 0-510 mM (Mateos-Naranjo et al 2010, Redondo-Go'mez et al 2011. Moreover, S. alterniflora can efficiently absorb water at high salinity because it's osmotic potential will increase with increasing salinity (Vasquez et al 2006).…”
Section: Effects Of Tolerance To Non-resource Stress On Plant Competimentioning
confidence: 99%
“…These studies however, did not take account of the potential interaction of Zn with other important factors characteristic of marshes ecosystems, particularly salinity. It has been demonstrated that the accumulation of sodium in another halophyte, Spartina densiflora, can mitigate its responses to Zn-induced stress (Redondo-Gómez et al, 2011). Hence knowledge of the extent to which salinity might modulate the physiological responses of J. acutus to excess Zn is necessary for a realistic assessment of its metal toxicity thresholds and its potential for the remediation of zinc-polluted saltmarshes.…”
Section: Introductionmentioning
confidence: 99%